Quality assurance and competitiveness of micro and small enterprises in the bakery and pastry sector - Bravo Aranibar, Juan Carlos (2023)
Quality assurance in food industries is a key factor, capable of redirecting micro and small enterprises (MSEs) towards obtaining food certifications with the objective of having a better future, based on the pillars of competitiveness, so that market globalization does not affect them. This article offers a literature review of quality assurance in relation to the dimensions of certification of general principles of food hygiene (PGH), certification of Hazard Analysis and Critical Control Points (HACCP), in addition to the certification of the quality management system (ISO 9001:2015) for the food sector. To determine competitiveness, the analysis is carried out in the following dimensions: productivity, technology, innovation, customer satisfaction, and public health. MSEs are the result of many years of work by entrepreneurs who, thanks to their effort and discipline, generate employment and are the future sources of employment for professionals.